Post dialysis osmotic demyelination syndrome: a case report - Mendieta, Melissa; Ramirez, Peter; Reyes, Gema; Mora, Mery; Mendoza, Dolores (International Journal of Research in Medical Sciences, 2025)
Osmotic demyelination syndrome (ODS) is a serious, irreversible, highly lethal clinical condition that is rarely described in the literature. It is caused by rapid correction of serum sodium, which generates abrupt changes in cerebrospinal fluid osmolarity, triggering neurological signs typical of this condition. It can occur due to rapid sodium correction through intravenous fluids and after emergent dialysis treatment in patients with renal pathologies, as described in this case; therefore, we consider it important to emphasize that dialysis treatment should be individualized based on a strict assessment of the internal environment for its correct correction, thus avoiding long-term sequelae and even death. We present a 38-year-old male patient with stage 5 chronic kidney disease, which did not allow dialysis treatment, admitted to a second-level hospital due to uremic encephalopathy and severe hyponatremia. During his stay in intensive care, he developed tonic-clonic seizures and neurological impairment, which began after emergency dialysis treatment, where rapid correction of trans dialytic serum sodium values was performed, generating classic neurological signs and imaging studies compatible with ODS.